(untitled) (Indian Journal of Arid Horticulture, 2025)
Custard apple is a climacteric fruit and highly perishable in nature as well as mostly utilized for fresh market. It has very short shelf life that makes the marketability difficult. Therefore, in the period of glut it has to be sold at unremunerative prices. Increasing shelf life of fruit is the only remedy for getting the remunerative profit from them. An investigation with bavistin, calcium carbide, Dithane M-45, oil emulsion (mustard oil, groundnut oil) and paraffin wax treatments were carried out. The application of Paraffin wax was found to be significantly better in physiological loss in weight (PLW), acidity, total soluble solids, reducing sugar and ripening of custard apple during storage.